Participatory Learning is Needed to Increase Family Independence in Handling Post-stroke Patients at Home - Ali Hamzah; Ihat Hatimah; Asep Saepudin; Joni Rahmat Pramudia; Khemaradee Masingboon (Universitas Negeri Semarang, 2024)
Post-stroke patients often experience dependency and disability due to paralysis and this really requires their families support to continue treatment at home. Currently, to carry out post-stroke treatment, they use homecare services because the family is less able to carry out post-stroke care independently at home. This research aims to identify an educational model that allows families to actively participate in learning so that they can be independent in treating post-stroke patients at home. The method used is mix method, involving 56 families of post-stroke patients selected by purposive sampling technique for quantitative data and two family members, two healthcare providers for qualitative data used in dept interview. The data quantitative were analyzed using the percentage formula which is presented in the form of a frequency distribution table, meanwhile qualitative data were processed by data reduction, presentation, and drawing conclusions. The results showed that most of the families of stroke patients didn’t receive and utilize homecare services for various reasons, including ignorance, inability and unpreparedness as well as inability to pay the costs. It is necessary to conduct research use the research and development (R & D) method with topics related to the development of homecare service models for post-stroke patients at home based on participatory learning. The novelty of this research is the production of a model design that can answer the needs of families to increase independence in treating post-stroke patients at home